A comprehensive method protocol for annotation and integrated functional understanding of lncRNAs - Kunz, Meik; Wolf, Beat; Fuchs, Maximilian; Christoph, Jan; Xiao, Ke; Thum, Thomas; Atlan, David; Prokosch, Hans-Ulrich; Dandekar, Thomas (Briefings in Bioinformatics, 2019)
Long non-coding RNAs (lncRNAs) are of fundamental biological importance; however, their functional role is often unclear or loosely defined as experimental characterization is challenging and bioinformatic methods are limited. We developed a novel integrated method protocol for the annotation and detailed functional characterization of lncRNAs within the genome. It combines annotation, normalization and gene expression with sequence-structure conservation, functional interactome and promoter analysis. Our protocol allows an analysis based on the tissue and biological context, and is powerful in functional characterization of experimental and clinical RNA-Seq datasets including existing lncRNAs. This is demonstrated on the uncharacterized lncRNA GATA6-AS1 in dilated cardiomyopathy.
EVALuna2:209483

Angiocrine Regulation of Epithelial Barrier Integrity in Inflammatory Bowel Disease - Stürzl, Michael; Kunz, Meik; Krug, Susanne M.; Naschberger, Elisabeth (Frontiers in Medicine, 2021)
Inflammatory bowel disease describes chronic inflammatory disorders. The incidence of the disease is rising. A major step in disease development is the breakdown of the epithelial cell barrier. Numerous blood vessels are directly located underneath this barrier. Diseased tissues are heavily vascularized and blood vessels significantly contribute to disease progression. The gut-vascular barrier (GVB) is an additional barrier controlling the entry of substances into the portal circulation and to the liver after passing the first epithelial barrier. The presence of the GVB rises the question, whether the vascular and endothelial barriers may communicate bi-directionally in the regulation of selective barrier permeability. Communication from epithelial to endothelial cells is well-accepted. In contrast, little is known on the respective backwards communication. Only recently, perfusion-independent angiocrine functions of endothelial cells were recognized in a way that endothelial cells release specific soluble factors that may directly act on the epithelial barrier. This review discusses the putative involvement of angiocrine inter-barrier communication in the pathogenesis of IBD.
CRIS-Team Scopus Importer:2021-08-27
Keywords: angiocrine; angiogenesis; barrier; endothelial; epithelial; inflammation; inflammatory bowel disease

Antifibrotic effects of specific targeting of the 5-hydroxytryptamine 2B receptor (5-HT2BR) in murine models and ex vivo models of scleroderma skin - Trinh-Minh, Thuong; Tran-Manh, Cuong; Györfi, Andrea Hermina; Dickel, Nicholas; Liebel, Christoph; Zhou, Xiang; Wang, Jiucun; Kunz, Meik; Arozenius, Helena; Pettersson, Lars; Lindgren, Sam; Wenglén, Christina; et al. (Arthritis and Rheumatology, 2025)
Objective: Systemic sclerosis (SSc) is a connective tissue disease with fibrotic remodeling of the skin and various internal organs. SSc is associated with the highest case-specific mortality of all rheumatic autoimmune diseases with limited antifibrotic treatment options. Here, we evaluated the therapeutic effects of the highly selective 5-hydroxytryptamine 2B receptor (5-HT2BR) inhibitor AM1476. Methods: The antifibrotic effects of AM1476 were evaluated in the mouse models of bleomycin-induced pulmonary fibrosis in Tsk-1 mice and in mice with sclerodermatous chronic graft-versus-host disease. For further validation, the antifibrotic effects of AM1476 were analyzed in precision cut skin (PCS) slices from patients with SSc. Results: AM1476 demonstrated high selectivity for 5-HT2BR over more than 200 other receptors, including other 5-HT receptors in vitro. AM1476 reduced accumulation of hydroxyproline and fibrotic tissue remodeling of skin and/or lungs in all three mouse models at well-tolerated doses with a comparable efficacy to that of nintedanib. In PCS of SSc skin, treatment with AM1476 reduced the expression of SSc-specific signature genes. AM1476 demonstrated more pronounced regulation of terms related to fibroblast activation and fibrotic remodeling than mycophenolate mofetil. Conclusion: We describe AM1476 as a highly selective inhibitor of 5-HT2BR. Treatment with AM1476 ameliorated fibrosis in three mouse models of SSc and normalized the expression of fibrosis-related genes directly in SSc skin. Because AM1476 also demonstrated good tolerability in a phase 1 trial, further clinical trials with AM1476 are currently in the planning stage.
CRIS-Team Scopus Importer:2025-05-30

Arginase 1 of myeloid cells accounts for disease chronicity in Leishmania mexicana-infected mice - Rai, Baplu; Debus, Andrea; Liang Chunguang; Kunz, Meik; Rauh, Manfred; Bogdan, Christian; Schleicher, Ulrike (EUROPEAN JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2022-03-11

Artificial Intelligence Identifies an Urgent Need for Peripheral Vascular Intervention by Multiplexing Standard Clinical Parameters - Sonnenschein, Kristina; Stojanovic, Stevan D.; Dickel, Nicholas; Fiedler, Jan; Bauersachs, Johann; Thum, Thomas; Kunz, Meik; Tongers, Joern (Biomedicines, 2021)
Background: Peripheral artery disease (PAD) is a significant burden, particularly among patients with severe disease requiring invasive treatment. We applied a general Machine Learning (ML) workflow and investigated if a multi-dimensional marker set of standard clinical parameters can identify patients in need of vascular intervention without specialized intra-hospital diagnostics. Methods: This is a retrospective study involving patients with stable PAD (sPAD, Fontaine Class I and II, n = 38) and unstable PAD (unPAD, Fontaine Class III and IV, n = 18) in need of invasive therapeutic measures. ML algorithms such as Random Forest were utilized to evaluate a matrix consisting of multiple routinely clinically available parameters (age, complete blood count, inflammation, lipid, iron metabolism). Results: ML has enabled a generation of an Artificial Intelligence (AI) PAD score (AI-PAD) that successfully divided sPAD from unPAD patients (high AI-PAD in sPAD, low AI-PAD in unPAD, cutoff at 50 AI-PAD units). Furthermore, the probability score positively coincided with gold-standard intra-hospital mean ankle-brachial index (ABI). Conclusion: AI-based tools may be promising to enable the correct identification of patients with unstable PAD by using existing clinical information, thus supplementing clinical decision making. Additional studies in larger prospective cohorts are necessary to determine the usefulness of this approach in comparison to standard diagnostic measures.
CRIS-Team WoS Importer:2021-11-19

A toolbox for functional analysis and the systematic identification of diagnostic and prognostic gene expression signatures combining meta-analysis and machine learning - Vey, Johannes; Kapsner, Lorenz; Fuchs, Maximilian; Unberath, Philipp; Veronesi, Giulia; Kunz, Meik (Cancers, 2019)
The identification of biomarker signatures is important for cancer diagnosis and prognosis. However, the detection of clinical reliable signatures is influenced by limited data availability, which may restrict statistical power. Moreover, methods for integration of large sample cohorts and signature identification are limited. We present a step-by-step computational protocol for functional gene expression analysis and the identification of diagnostic and prognostic signatures by combining meta-analysis with machine learning and survival analysis. The novelty of the toolbox lies in its all-in-one functionality, generic design, and modularity. It is exemplified for lung cancer, including a comprehensive evaluation using different validation strategies. However, the protocol is not restricted to specific disease types and can therefore be used by a broad community. The accompanying R package vignette runs in 1 h and describes the workflow in detail for use by researchers with limited bioinformatics training.
CRIS-Team Scopus Importer:2019-11-22
Keywords: Bioinformatics tool; Biomarker signature; Functional analysis; Gene expression analysis; Machine learning; Meta-analysis; R package; Survival analysis

Attenuation of fibroblast activation and fibrosis by adropin in systemic sclerosis - Liang, Minrui; Dickel, Nicholas; Györfi, Andrea Hermina; SafakTümerdem, Bilgesu; Li, Yi Nan; Rius Rigau, Aleix Rius; Liang, Chunguang; Hong, Xuezhi; Shen, Lichong; Matei, Alexandru-Emil; Trinh-Minh, Thuong; Tran-Manh, Cuong; et al. (Science Translational Medicine, 2024)
Fibrotic diseases impose a major socioeconomic challenge on modern societies and have limited treatment options. Adropin, a peptide hormone encoded by the energy homeostasis–associated (ENHO) gene, is implicated in metabolism and vascular homeostasis, but its role in the pathogenesis of fibrosis remains enigmatic. Here, we used machine learning approaches in combination with functional in vitro and in vivo experiments to characterize adropin as a potential regulator involved in fibroblast activation and tissue fibrosis in systemic sclerosis (SSc). We demonstrated consistent down-regulation of adropin/ENHO in skin across multiple cohorts of patients with SSc. The prototypical profibrotic cytokine TGFβ reduced adropin/ENHO expression in a JNK-dependent manner. Restoration of adropin signaling by therapeutic application of bioactive adropin34–76 peptides in turn inhibited TGFβ-induced fibroblast activation and fibrotic tissue remodeling in primary human dermal fibroblasts, three-dimensional full-thickness skin equivalents, mouse models of bleomycin-induced pulmonary fibrosis and sclerodermatous chronic graft-versus-host-disease (sclGvHD), and precision-cut human skin slices. Knockdown of GPR19, an adropin receptor, abrogated the antifibrotic effects of adropin in fibroblasts. RNA-seq demonstrated that the antifibrotic effects of adropin34–76 were functionally linked to deactivation of GLI1-dependent profibrotic transcriptional networks, which was experimentally confirmed in vitro, in vivo, and ex vivo using cultured human dermal fibroblasts, a sclGvHD mouse model, and precision-cut human skin slices. ChIP-seq confirmed adropin34–76-induced changes in TGFβ/GLI1 signaling. Our study characterizes the TGFβ-induced down-regulation of adropin/ENHO expression as a potential pathomechanism of SSc as a prototypical systemic fibrotic disease that unleashes uncontrolled activation of profibrotic GLI1 signaling.
CRIS-Team Scopus Importer:2024-04-05

Bioinformatics: An Introductory Textbook - Dandekar, Thomas; Kunz, Meik (Springer Berlin Heidelberg, 2023)
This book offers a gripping introduction to the fastest growing field of biology with easy-to-follow examples and a well-prepared appendix for the reader to cook up and experience everything right away. The book gets the reader started with the basics, such as how to easily find sequence information and then analyze it. In further chapters, the authors go into the various analysis options from RNA, DNA and proteins to entire metabolic pathways. Exciting examples from biology are chosen in each chapter to illustrate the analysis. Each chapter concludes with an exercise section that immediately puts what has been learned to use. The subject of this book is a must for any biology student, whether undergraduate or graduate, as bioinformatics is now unearthing amazing insights into the molecular basis of all living things. Computer science students and other students from related sciences will get a good introduction to bioinformatics, as biology and current topics (e.g. AI) are systematically introduced step by step alongside the software. Discover the key to life together with the authors and learn to understand the language of life. This book is a translation of the original German 2nd edition Bioinformatik by Thomas Dandekar and Meik Kunz, published by Springer-Verlag GmbH Germany, part of Springer Nature in 2021. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation. Springer Nature works continuously to further the development of tools for the production of books and on the related technologies to support the authors.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Bioinformatics; Biomedicine; Computer; Information; Life; Systems Biology

Blocking IL-1, IL-33 and IL-36 Signaling with the Anti-IL1RAP Antibody mCAN10 Ameliorates Inflammation and Fibrosis in Preclinical Models of Systemic Sclerosis - Gronberg, Caitriona; Rattik, Sara; Kunz, Meik; Thoung Trinh-Minh; Tran Manh, Cuong; Zhou, Xiang; Skoog, Petter; Liberg, David; Distler, Jörg (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

CD137 (4-1BB) stimulation leads to metabolic and functional reprogramming of human monocytes/macrophages enhancing their tumoricidal activity - Stoll, Andrej; Bruns, Heiko; Fuchs, Maximilian; Nimmerjahn, Falk; Kunz, Meik; Peipp, M.; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (Leukemia, 2021)
Immunotherapies have heralded a new era in the cancer treatment. In addition to checkpoint inhibitors, agonistic antibodies against co-stimulatory immune receptors hold the potential to invoke efficient antitumor immunity. Targeting CD137 has gained momentum based on its ability to drive NK- and T-cell-based responses. CD137-engaging mAbs have already entered clinical trials for different types of tumors showing promising results. Despite the efforts to translate CD137-mediated immunotherapy into clinical practice, little remains known regarding the role of CD137 in human monocytes/macrophages. We found CD137 being expressed on monocytes of healthy controls and at even higher levels in patients with multiple myeloma or CLL. CD137HI(GH) monocytes displayed a distinct phenotypic, transcriptomic, and metabolic profile. They possessed an increased phagocytic capacity enabling superior antibody-dependent phagocytosis (ADPC) of multiple myeloma and lymphoma cells that were treated with anti-CD38 or anti-CD20 mAbs. Triggering CD137 promoted both metabolic and tumoricidal activity in an extracellular signal-regulated kinase (ERK)-dependent fashion. In addition, we observed a phenotypic, transcriptomic, and functional skewing towards a M1-like phenotype. Overall, we introduce CD137 as a positive immune checkpoint on human monocytes/macrophages, which can have therapeutic implications especially in view of synergistic effects when combining CD137 agonists with tumor-targeting antibodies.
CRIS-Team Scopus Importer:2021-06-04

CD137 (4-1BB) triggering leads to metabolic and functional reprogramming of human monocytes/macrophages enhancing their tumoricidal activity - Stoll, Andrej; Bruns, Heiko; Gamali, S.; Saul, Domenica; Fuchs, Maximilian; Nimmerjahn, Falk; Kunz, Meik; Peipp, M.; Mackensen, Andreas; Mougiakakos, Dimitrios (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Chagas Disease: Detection of Trypanosoma cruzi by a New, High-Specific Real Time PCR - Kann, Simone; Kunz, Meik; Hansen, Jessica; Sievertsen, Juergen; Crespo, Jose J.; Loperena, Aristides; Arriens, Sandra; Dandekar, Thomas (Journal of Clinical Medicine, 2020)
Background: Chagas disease (CD) is a major burden in Latin America, expanding also to non-endemic countries. A gold standard to detect the CD causing pathogen Trypanosoma cruzi is currently not available. Existing real time polymerase chain reactions (RT-PCRs) lack sensitivity and/or specificity. We present a new, highly specific RT-PCR for the diagnosis and monitoring of CD. Material and Methods: We analyzed 352 serum samples from Indigenous people living in high endemic CD areas of Colombia using three leading RT-PCRs (k-DNA-, TCZ-, 18S rRNA-PCR), the newly developed one (NDO-PCR), a Rapid Test/enzyme-linked immuno sorbent assay (ELISA), and immunofluorescence. Eighty-seven PCR-products were verified by sequence analysis after plasmid vector preparation. Results: The NDO-PCR showed the highest sensitivity (92.3%), specificity (100%), and accuracy (94.3%) for T. cruzi detection in the 87 sequenced samples. Sensitivities and specificities of the kDNA-PCR were 89.2%/22.7%, 20.5%/100% for TCZ-PCR, and 1.5%/100% for the 18S rRNA-PCR. The kDNA-PCR revealed a 77.3% false positive rate, mostly due to cross-reactions with T. rangeli (NDO-PCR 0%). TCZ- and 18S rRNA-PCR showed a false negative rate of 79.5% and 98.5% (NDO-PCR 7.7%), respectively. Conclusions: The NDO-PCR demonstrated the highest specificity, sensitivity, and accuracy compared to leading PCRs. Together with serologic tests, it can be considered as a reliable tool for CD detection and can improve CD management significantly.
CRIS-Team WoS Importer:2020-06-26

Combined inhibition of IL-1, IL-33 and IL-36 signalling by targeting IL1RAP ameliorates skin and lung fibrosis in preclinical models of systemic sclerosis - Grönberg, Caitríona; Rattik, Sara; Tran-Manh, Cuong; Zhou, Xiang; Rius Rigau, Aleix Rius; Li, Yi Nan; Györfi, Andrea Hermina; Dickel, Nicholas; Kunz, Meik; Kreuter, Alexander; Matei, Emil Alexandru; Zhu, Honglin; et al. (Annals of the Rheumatic Diseases, 2024)
Background: The interleukin (IL)-1 receptor accessory protein (IL1RAP) is an essential coreceptor required for signalling through the IL-1, IL-33 and IL-36 receptors. Here, we investigate the antifibrotic potential of the combined inhibition of these cytokines by an anti-IL1RAP antibody to provide a scientific background for clinical development in systemic sclerosis (SSc). Methods: The expression of IL1RAP-associated signalling molecules was determined by data mining of publicly available RNA sequencing (RNAseq) data as well as by imaging mass cytometry. The efficacy of therapeutic dosing of anti-IL1RAP antibodies was determined in three complementary mouse models: sclerodermatous chronic graft-versus-host disease (cGvHD), bleomycin-induced dermal fibrosis model and topoisomerase-I (topo)-induced fibrosis. Results: SSc skin showed upregulation of IL1RAP and IL1RAP-related signalling molecules on mRNA and protein level compared with normal skin. IL-1, IL-33 and IL-36 all regulate distinct gene sets related to different pathophysiological processes in SSc. The responses of human fibroblasts and endothelial cells to IL-1, IL-33 and IL-36 were completely blocked by treatment with an anti-IL1RAP antibody in vitro. Moreover, anti-IL1RAP antibody treatment reduced dermal and pulmonary fibrosis in cGvHD-induced, bleomycin-induced and topoisomerase-induced fibrosis. Importantly, RNAseq analyses revealed effects of IL1RAP inhibition on multiple processes related to inflammation and fibrosis that are also deregulated in human SSc skin. Conclusion: This study provides the first evidence for the therapeutic benefits of targeting IL1RAP in SSc. Our findings have high translational potential as the anti-IL1RAP antibody CAN10 has recently entered a phase one clinical trial.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Fibroblasts; Inflammation; Pulmonary Fibrosis; Scleroderma; Systemic

Comprehensive bioinformatics identifies key microrNA players in ATG7-deficient lung fibroblasts - Stojanović, Stevan D.; Fuchs, Maximilian; Fiedler, Jan; Xiao, Ke; Meinecke, Anna; Just, Annette; Pich, Andreas; Thum, Thomas; Kunz, Meik (International Journal of Molecular Sciences, 2020)
Background: Deficient autophagy has been recently implicated as a driver of pulmonary fibrosis, yet bioinformatics approaches to study this cellular process are lacking. Autophagy-related 5 and 7 (ATG5/ATG7) are critical elements of macro-autophagy. However, an alternative ATG5/ATG7-independent macro-autophagy pathway was recently discovered, its regulation being unknown. Using a bioinformatics proteome profiling analysis of ATG7-deficient human fibroblasts, we aimed to identify key microRNA (miR) regulators in autophagy. Method: We have generated ATG7-knockout MRC-5 fibroblasts and performed mass spectrometry to generate a large-scale proteomics dataset. We further quantified the interactions between various proteins combining bioinformatics molecular network reconstruction and functional enrichment analysis. The predicted key regulatory miRs were validated via quantitative polymerase chain reaction. Results: The functional enrichment analysis of the 26 deregulated proteins showed decreased cellular trafficking, increased mitophagy and senescence as the major overarching processes in ATG7-deficient lung fibroblasts. The 26 proteins reconstitute a protein interactome of 46 nodes and miR-regulated interactome of 834 nodes. The miR network shows three functional cluster modules around miR16-5p, miR-17-5p and let-7a related to multiple deregulated proteins. Confirming these results in a biological setting, serially passaged wild-type and autophagy-deficient fibroblasts displayed senescence-dependent expression profiles of miR-16-5p and miR-17-5p. Conclusions: We have developed a bioinformatics proteome profiling approach that successfully identifies biologically relevant miR regulators from a proteomics dataset of the ATG-7-deficient milieu in lung fibroblasts, and thus may be used to elucidate key molecular players in complex fibrotic pathological processes. The approach is not limited to a specific cell-type and disease, thus highlighting its high relevance in proteome and non-coding RNA research.
CRIS-Team Scopus Importer:2020-06-19
Keywords: Autophagy; Bioinformatics; Functional network analysis; Lung fibrosis; MiR; Proteomics; Senescence

Comprehensive bone marrow analysis integrating deep learning-based pattern discovery (BMDeep) - Pontones, Martina; Hoefener, H.; Kock, F.; Schwen, L.; Westphal, M.; Dickel, Nicholas; Kunz, Meik; Metzler, Markus (KLINISCHE PADIATRIE, 2022)
Bone marrow morphology forms the basis for the assessment of hematopoiesis. The currently established approach is dependent on manual microscopic counting of a limited number of cells by specially trained personnel, which is inherently associated with substantial intra- and inter-individual variability. The aim of our project is to automatize and improve the evaluation of bone marrow smears and to identify pathological patterns in pediatric leukemia.<br
CRIS-Team WoS Importer:2022-07-08

Connecting cancer pathways to tumor engines: A stratification tool for colorectal cancer combining human in vitro tissue models with boolean in silico models - Baur, Florentin; Nietzer, Sarah L.; Kunz, Meik; Saal, Fabian; Jeromin, Julian; Matschos, Stephanie; Linnebacher, Michael; Walles, Heike; Dandekar, Thomas; Dandekar, Gudrun (Cancers, 2020)
To improve and focus preclinical testing, we combine tumor models based on a decellularized tissue matrix with bioinformatics to stratify tumors according to stage-specific mutations that are linked to central cancer pathways. We generated tissue models with BRAF-mutant colorectal cancer (CRC) cells (HROC24 and HROC87) and compared treatment responses to two-dimensional (2D) cultures and xenografts. As the BRAF inhibitor vemurafenib is—in contrast to melanoma—not effective in CRC, we combined it with the EGFR inhibitor gefitinib. In general, our 3D models showed higher chemoresistance and in contrast to 2D a more active HGFR after gefitinib and combination-therapy. In xenograft models murine HGF could not activate the human HGFR, stressing the importance of the human microenvironment. In order to stratify patient groups for targeted treatment options in CRC, an in silico topology with different stages including mutations and changes in common signaling pathways was developed. We applied the established topology for in silico simulations to predict new therapeutic options for BRAF-mutated CRC patients in advanced stages. Our in silico tool connects genome information with a deeper understanding of tumor engines in clinically relevant signaling networks which goes beyond the consideration of single drivers to improve CRC patient stratification.
CRIS-Team Scopus Importer:2020-02-04
Keywords: 3D tissue models; BRAF mutation; Colorectal cancer; In silico simulation; Stratification; Targeted therapy

Deciphering Pro-angiogenic Transcription Factor Profiles in Hypoxic Human Endothelial Cells by Combined Bioinformatics and in vitro Modeling - Schmidt, Arne; Fuchs, Maximilian; Stojanović, Stevan D.; Liang, Chunguang; Schmidt, Kevin; Jung, Mira; Xiao, Ke; Weusthoff, Jan; Just, Annette; Pfanne, Angelika; Distler, Jörg; Dandekar, Thomas; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Constant supply of oxygen is crucial for multicellular tissue homeostasis and energy metabolism in cardiac tissue. As a first response to acute hypoxia, endothelial cells (ECs) promote recruitment and adherence of immune cells to the dysbalanced EC barrier by releasing inflammatory mediators and growth factors, whereas chronic hypoxia leads to the activation of a transcription factor (TF) battery, that potently induces expression of growth factors and cytokines including platelet-derived growth factor (PDGF) and vascular endothelial growth factor (VEGF). We report a hypoxia-minded, targeted bioinformatics approach aiming to identify and validate TFs that regulate angiogenic signaling. Results: A comprehensive RNA-Seq dataset derived from human ECs subjected to normoxic or hypoxic conditions was selected to identify significantly regulated genes based on (i) fold change (normoxia vs. hypoxia) and (ii) relative abundancy. Transcriptional regulation of this gene set was confirmed via qPCR in validation experiments where HUVECs were subjected to hypoxic conditions for 24 h. Screening the promoter and upstream regulatory elements of these genes identified two TFs, KLF5 and SP1, both with a potential binding site within these regions of selected target genes. In vitro, siRNA experiments confirmed SP1- and KLF5-mediated regulation of identified hypoxia-sensitive endothelial genes. Next to angiogenic signaling, we also validated the impact of TFs on inflammatory signaling, both key events in hypoxic sensing. Both TFs impacted on inflammatory signaling since endogenous repression led to increased NF-κB signaling. Additionally, SP1 silencing eventuated decreased angiogenic properties in terms of proliferation and tube formation. Conclusion: By detailed in silico analysis of promoter region and upstream regulatory elements for a list of hypoxia-sensitive genes, our bioinformatics approach identified putative binding sites for TFs of SP or KLF family in vitro. This strategy helped to identify TFs functionally involved in human angiogenic signaling and therefore serves as a base for identifying novel RNA-based drug entities in a therapeutic setting of vascularization.
CRIS-Team Scopus Importer:2022-10-28
Keywords: angiogenesis; endothelial; hypoxia; promoter profiling; signaling; transcription factor

Effect of Anti-S100A4 Monoclonal Antibody Treatment on Experimental Skin Fibrosis and Systemic Sclerosis–Specific Transcriptional Signatures in Human Skin - Trinh-Minh, Thuong; Györfi, Andrea Hermina; Tomcik, Michal; Tran-Manh, Cuong; Zhou, Xiang; Dickel, Nicholas; Tümerdem, Bilgesu Safak; Kreuter, Alexander; Burmann, Sven Niklas; Borchert, Signe Vedel; Hussain, Rizwan Iqbal; Hallén, Jonas; et al. (Arthritis and Rheumatology, 2024)
Objective: S100A4 is a DAMP protein. S100A4 is overexpressed in patients with systemic sclerosis (SSc), and levels correlate with organ involvement and disease activity. S100A4−/− mice are protected from fibrosis. The aim of this study was to assess the antifibrotic effects of anti-S100A4 monoclonal antibody (mAb) in murine models of SSc and in precision cut skin slices of patients with SSc. Methods: The effects of anti-S100A4 mAbs were evaluated in a bleomycin-induced skin fibrosis model and in Tsk-1 mice with a therapeutic dosing regimen. In addition, the effects of anti-S100A4 mAbs on precision cut SSc skin slices were analyzed by RNA sequencing. Results: Inhibition of S100A4 was effective in the treatment of pre-established bleomycin-induced skin fibrosis and in regression of pre-established fibrosis with reduced dermal thickening, myofibroblast counts, and collagen accumulation. Transcriptional profiling demonstrated targeting of multiple profibrotic and proinflammatory processes relevant to the pathogenesis of SSc on targeted S100A4 inhibition in a bleomycin-induced skin fibrosis model. Moreover, targeted S100A4 inhibition also modulated inflammation- and fibrosis-relevant gene sets in precision cut SSc skin slices in an ex vivo trial approach. Selected downstream targets of S100A4, such as AMP-activated protein kinase, calsequestrin-1, and phosphorylated STAT3, were validated on the protein level, and STAT3 inhibition was shown to prevent the profibrotic effects of S100A4 on fibroblasts in human skin. Conclusion: Inhibition of S100A4 confers dual targeting of inflammatory and fibrotic pathways in complementary mouse models of fibrosis and in SSc skin. These effects support the further development of anti-S100A4 mAbs as disease-modifying targeted therapies for SSc.
CRIS-Team Scopus Importer:2024-05-10

ENGRAILED 1 COORDINATES CYTOSKELETAL ORGANIZATION TO PROMOTE MYOFIBROBLAST DIFFERENTIATION AND FIBROTIC TISSUE REMODELING - Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Fuchs, Maximilian; Rigau, Aleix; Hong, Xuezhi; Honglin, Z.; Luber, M.; Bergmann, Christina; Dees, Clara; Ludolph, Ingo; Horch, Raymund E.; Distler, O.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-10-01

Engrailed 1 coordinates cytoskeletal reorganization to induce myofibroblast differentiation - Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Fuchs, Maximilian; Liang, Chunguang; Rigau, Aleix; Hong, Xuezhi; Zhu, Honglin; Luber, Markus; Bergmann, Christina; Dees, Clara; Ludolph, Ingo; Horch, Raymund E.; et al. (Journal of Experimental Medicine, 2021)
Transforming growth factor-β (TGFβ) is a key mediator of fibroblast activation in fibrotic diseases, including systemic sclerosis. Here we show that Engrailed 1 (EN1) is reexpressed in multiple fibroblast subpopulations in the skin of SSc patients. We characterize EN1 as a molecular amplifier of TGFβ signaling in myofibroblast differentiation: TGFβ induces EN1 expression in a SMAD3-dependent manner, and in turn, EN1 mediates the profibrotic effects of TGFβ. RNA sequencing demonstrates that EN1 induces a profibrotic gene expression profile functionally related to cytoskeleton organization and ROCK activation. EN1 regulates gene expression by modulating the activity of SP1 and other SP transcription factors, as confirmed by ChIP-seq experiments for EN1 and SP1. Functional experiments confirm the coordinating role of EN1 on ROCK activity and the reorganization of cytoskeleton during myofibroblast differentiation, in both standard fibroblast culture systems and in vitro skin models. Consistently, mice with fibroblast-specific knockout of En1 demonstrate impaired fibroblast-to-myofibroblast transition and are partially protected from experimental skin fibrosis.
CRIS-Team Scopus Importer:2021-07-30

IL-33-induced metabolic reprogramming controls the differentiation of alternatively activated macrophages and the resolution of inflammation - Faas, Maria; Ipseiz, Natacha; Ackermann, Jochen; Culemann, Stephan; Grüneboom, Anika; Schröder, Fenja; Rothe, Tobias; Scholtysek, Carina; Eberhardt, Martin; Böttcher, Martin; Kirchner, Philipp; Stoll, Cornelia; et al. (Immunity, 2021)
Alternatively activated macrophages (AAMs) contribute to the resolution of inflammation and tissue repair. However, molecular pathways that govern their differentiation have remained incompletely understood. Here, we show that uncoupling protein-2-mediated mitochondrial reprogramming and the transcription factor GATA3 specifically controlled the differentiation of pro-resolving AAMs in response to the alarmin IL-33. In macrophages, IL-33 sequentially triggered early expression of pro-inflammatory genes and subsequent differentiation into AAMs. Global analysis of underlying signaling events revealed that IL-33 induced a rapid metabolic rewiring of macrophages that involved uncoupling of the respiratory chain and increased production of the metabolite itaconate, which subsequently triggered a GATA3-mediated AAM polarization. Conditional deletion of GATA3 in mononuclear phagocytes accordingly abrogated IL-33-induced differentiation of AAMs and tissue repair upon muscle injury. Our data thus identify an IL-4-independent and GATA3-dependent pathway in mononuclear phagocytes that results from mitochondrial rewiring and controls macrophage plasticity and the resolution of inflammation.
CRIS-Team Scopus Importer:2021-11-19
Keywords: alternatively activated macrophage; GATA3; interleukin-33; itaconate; mitochondrial rewiring; resolution of inlammation; UCP2; uncoupling

Immunoglobulin G-dependent inhibition of inflammatory bone remodeling requires pattern recognition receptor Dectin-1 - Seeling, Michaela; Pöhnl, Matthias; Kara, Sibel; Horstmann, Nathalie; Riemer, Carolina; Wöhner, Miriam; Liang, Chunguang; Brückner, Christin; Eiring, Patrick; Werner, Anja; Biburger, Markus; Altmann, Leon; et al. (Immunity, 2023)
Immunoglobulin G (IgG) antibodies are major drivers of inflammation during infectious and autoimmune diseases. In pooled serum IgG (IVIg), however, antibodies have a potent immunomodulatory and anti-inflammatory activity, but how this is mediated is unclear. We studied IgG-dependent initiation of resolution of inflammation in cytokine- and autoantibody-driven models of rheumatoid arthritis and found IVIg sialylation inhibited joint inflammation, whereas inhibition of osteoclastogenesis was sialic acid independent. Instead, IVIg-dependent inhibition of osteoclastogenesis was abrogated in mice lacking receptors Dectin-1 or FcγRIIb. Atomistic molecular dynamics simulations and super-resolution microscopy revealed that Dectin-1 promoted FcγRIIb membrane conformations that allowed productive IgG binding and enhanced interactions with mouse and human IgG subclasses. IVIg reprogrammed monocytes via FcγRIIb-dependent signaling that required Dectin-1. Our data identify a pathogen-independent function of Dectin-1 as a co-inhibitory checkpoint for IgG-dependent inhibition of mouse and human osteoclastogenesis. These findings may have implications for therapeutic targeting of autoantibody and cytokine-driven inflammation.
CRIS-Team Scopus Importer:2023-05-12
Keywords: bone; Dectin-1; Fc-receptor; glycosylation; IgG; inflammation; osteoclast; rheumatoid arthritis

Inflammatory Drivers of Cardiovascular Disease: Molecular Characterization of Senescent Coronary Vascular Smooth Muscle Cells - Stojanović, Stevan D.; Fuchs, Maximilian; Kunz, Meik; Xiao, Ke; Just, Annette; Pich, Andreas; Bauersachs, Johann; Fiedler, Jan; Sedding, Daniel; Thum, Thomas (Frontiers in Physiology, 2020)
The senescence of vascular smooth muscle cells (VSMCs) has been implicated as a causal pro-inflammatory mechanism for cardiovascular disease development and progression of atherosclerosis, the instigator of ischemic heart disease. Contemporary limitations related to studying this cellular population and senescence-related therapeutics are caused by a lack of specific markers enabling their detection. Therefore, we aimed to profile a phenotypical and molecular signature of senescent VSMCs to allow reliable identification. To achieve this goal, we have compared non-senescent and senescent VSMCs from two in vitro models of senescence, replicative senescence (RS) and DNA-damage induced senescence (DS), by analyzing the expressions of established senescence markers: cell cycle inhibitors- p16 INK4a, p14 ARF, p21 and p53; pro-inflammatory factors-Interleukin 1β (IL-1β), IL-6 and high mobility group box-1 (HMGB-1); contractile proteins-smooth muscle heavy chain- (MYH11), smoothelin and transgelin (TAGLN), as well as structural features (nuclear morphology and LMNB1 (Lamin B1) expression). The different senescence-inducing modalities resulted in a lack of the proliferative activity. Nucleomegaly was seen in senescent VSMC as compared to freshly isolated VSMC Phenotypically, senescent VSMC appeared with a significantly larger cell size and polygonal, non-spindle-shaped cell morphology. In line with the supposed switch to a pro-inflammatory phenotype known as the senescence associated secretory phenotype (SASP), we found that both RS and DS upregulated IL-1β and released HMGB-1 from the nucleus, while RS also showed IL-6 upregulation. In regard to cell cycle-regulating molecules, we detected modestly increased p16 levels in both RS and DS, but largely inconsistent p21, p14ARF, and p53 expressions in senescent VSMCs. Since these classical markers of senescence showed insufficient deregulation to warrant senescent VSMC detection, we have conducted a non-biased proteomics and in silico analysis of RS VSMC demonstrating altered RNA biology as the central molecular feature of senescence in this cell type. Therefore, key proteins involved with RNA functionality, HMGB-1 release, LMNB-1 downregulation, in junction with nuclear enlargement, can be used as markers of VSMC senescence, enabling the detection of these pathogenic pro-inflammatory cells in future therapeutic studies in ischemic heart disease and atherosclerosis.
CRIS-Team Scopus Importer:2020-06-16
Keywords: aging; cardiovascular; inflammation; senescence; smooth muscle cell

In silico signaling modeling to understand cancer pathways and treatment responses - Kunz, Meik; Jeromin, Julian; Fuchs, Maximilian; Christoph, Jan; Veronesi, Giulia; Flentje, Michael; Nietzer, Sarah L.; Dandekar, Gudrun; Dandekar, Thomas (Briefings in Bioinformatics, 2019)
Precision medicine has changed thinking in cancer therapy, highlighting a better understanding of the individual clinical interventions. But what role do the drivers and pathways identified from pan-cancer genome analysis play in the tumor? In this letter, we will highlight the importance of in silico modeling in precision medicine. In the current era of big data, tumor engines and pathways derived from pan-cancer analysis should be integrated into in silico models to understand the mutational tumor status and individual molecular pathway mechanism at a deeper level. This allows to pre-evaluate the potential therapy response and develop optimal patient-tailored treatment strategies which pave the way to support precision medicine in the clinic of the future.
EVALuna2:209496

Integrative bioinformatic analyses of global transcriptome data decipher novel molecular insights into cardiac anti-fibrotic therapies - Fuchs, Maximilian; Kreutzer, Fabian Philipp; Kapsner, Lorenz; Mitzka, Saskia; Just, Annette; Perbellini, Filippo; Terracciano, Cesare M.; Xiao, Ke; Geffers, Robert; Bogdan, Christian; Prokosch, Hans-Ulrich; Fiedler, Jan; et al. (International Journal of Molecular Sciences, 2020)
Integrative bioinformatics is an emerging field in the big data era, offering a steadily increasing number of algorithms and analysis tools. However, for researchers in experimental life sciences it is often difficult to follow and properly apply the bioinformatical methods in order to unravel the complexity and systemic effects of omics data. Here, we present an integrative bioinformatics pipeline to decipher crucial biological insights from global transcriptome profiling data to validate innovative therapeutics. It is available as a web application for an interactive and simplified analysis without the need for programming skills or deep bioinformatics backgroundThe approach was applied to an ex vivo cardiac model treated with natural anti-fibrotic compounds and we obtained new mechanistic insights into their anti-fibrotic action and molecular interplay with miRNAs in cardiac fibrosis. Several gene pathways associated with proliferation, extracellular matrix processes and wound healing were altered, and we could identify micro (mi) RNA-21-5p and miRNA-223-3p as key molecular components related to the anti-fibrotic treatment. Importantlyour pipeline is not restricted to a specific cell type or disease and can be broadly applied to better understand the unprecedented level of complexity in big data research.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Algorithm; Big data; Cardiac fibrosis; Integrative bioinformatics; MiRNAs; Natural compounds; Transcriptomics; Web application

L-Arginine metabolism inhibits arthritis and inflammatory bone loss - Cao, Shan; Li, Yixuan; Song, Rui; Meng, Xianyi; Fuchs, Maximilian; Liang, Chunguang; Kachler, Katerina; Meng, Xinyu; Wen, Jinming; Schlötzer-Schrehardt, Ursula; Taudte, Verena; Geßner, Arne; et al. (Annals of the Rheumatic Diseases, 2023)
Objectives: To investigate the effect of the L-Arginine metabolism on arthritis and inflammation-mediated bone loss. Methods: L-Arginine was applied to three arthritis models (collagen-induced arthritis, serum-induced arthritis and human TNF transgenic mice). Inflammation was assessed clinically and histologically, while bone changes were quantified by μCT and histomorphometry. In vitro, effects of L-Arginine on osteoclast differentiation were analysed by RNA-seq and mass spectrometry (MS). Seahorse, Single Cell ENergetIc metabolism by profilIng Translation inHibition and transmission electron microscopy were used for detecting metabolic changes in osteoclasts. Moreover, arginine-Associated metabolites were measured in the serum of rheumatoid arthritis (RA) and pre-RA patients. Results: L-Arginine inhibited arthritis and bone loss in all three models and directly blocked TNFα-induced murine and human osteoclastogenesis. RNA-seq and MS analyses indicated that L-Arginine switched glycolysis to oxidative phosphorylation in inflammatory osteoclasts leading to increased ATP production, purine metabolism and elevated inosine and hypoxanthine levels. Adenosine deaminase inhibitors blocking inosine and hypoxanthine production abolished the inhibition of L-Arginine on osteoclastogenesis in vitro and in vivo. Altered arginine levels were also found in RA and pre-RA patients. Conclusion: Our study demonstrated that L-Arginine ameliorates arthritis and bone erosion through metabolic reprogramming and perturbation of purine metabolism in osteoclasts.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Arthritis; Inflammation; Osteoporosis

L-ARGININE REPROGRAMS OSTEOCLAST PURINE METABOLISM AMELIORATING BONE LOSS IN RHEUMATOID ARTHRITIS - Cao, Shan; Song, Rui; Meng, Xianyi; Kachler, Katerina; Fuchs, Maximilian; Meng, X.; Li, Y.; Taudte, Verena; Kunz, Meik; Schlötzer-Schrehardt, Ursula; Schleicher, Ulrike; Chen, X.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Modular micro-physiological human tumor/tissue models based on decellularized tissue for improved preclinical testing - Kühnemundt, Johanna; Leifeld, Heidi; Scherg, Florian; Schmitt, Matthias; Nelke, Lena C.; Schmitt, Tina; Baur, Florentin; Göttlich, Claudia; Fuchs, Maximilian; Kunz, Meik; Peindl, Matthias; Brähler, Caroline; et al. (Alternatives To Animal Experimentation, 2021)
High attrition rates associated with drug testing in 2D cell culture and animal models stress the need for improved modeling of human tumor tissues. In previous studies, our 3D models on a decellularized tissue matrix have shown better predictivity and higher chemoresistance. A single porcine intestine yields material for 150 3D models of breast, lung, colorectal cancer (CRC) or leukemia. The uniquely preserved structure of the basement membrane enables physiological anchorage of endothelial cells and epithelial-derived carcinoma cells. The matrix provides different niches for cell growth: on top as monolayer, in crypts as aggregates, and within deeper layers. Dynamic culture in bioreactors enhances cell growth. Comparing gene expression between 2D and 3D cultures, we observed changes related to proliferation, apoptosis and stemness. For drug target predictions, we utilize tumor-specific sequencing data in our in silico model, finding an additive effect of metformin and gefitinib treatment for lung cancer in silico, validated in vitro. To analyze mode-of-action, immune therapies such as trispecific T-cell engagers in leukemia or toxicity on non-cancer cells, the model can be modularly enriched with human endothelial cells (hECs), immune cells and fibroblasts. Upon addition of hECs, transmigration of immune cells through the endothelial barrier can be investigated. In an allogenic CRC model, we observe a lower basic apoptosis rate after applying PBMCs in 3D compared to 2D, which offers new options to mirror antigen-specific immunotherapies in vitro. In conclusion, we present modular human 3D tumor models with tissue-like features for preclinical testing to reduce animal experiments.
CRIS-Team Scopus Importer:2021-05-14

Mutual Amplification of GLI2/Hedgehog and Transcription Factor JUN/AP-1 Signaling in Fibroblasts in Systemic Sclerosis: Potential Implications for Combined Therapies - Bergmann, Christina; Chenguiti Fakhouri, Sara; Trinh-Minh, Thuong; Filla, Tim; Rius Rigau, Aleix Rius; Ekici, Arif Bülent; Merlevede, Benita; Hallenberger, Ludwig; Zhu, Honglin; Dees, Clara; Matei, Alexandru Emil; Auth, Janina; et al. (Arthritis and Rheumatology, 2024)
Objective: Deregulation of the cJUN/AP-1 and hedgehog/GLI2 signaling pathways has been implicated in fibroblast activation in systemic sclerosis (SSc). However, the consequences of their concomitant up-regulation are unknown. Here, we tested the hypothesis that mutual amplification of both pathways might drive persistent fibroblast activation. Methods: Cultured fibroblasts and skin sections of patients with diffuse SSc and healthy volunteers were analyzed. cJUN/AP-1 signaling and hedgehog/GLI2 signaling were inhibited using knockdown and pharmacologic approaches. Hedgehog signaling was activated in mice by fibroblast-specific overexpression of constitutively active Smoothened. Results: cJUN and GLI2 are concomitantly up-regulated and colocalize in fibroblasts of patients with SSc compared to healthy controls. Activation of hedgehog/GLI2 signaling induces the expression of cJUN in vitro and in vivo, whereas inactivation of GLI2 inhibits cJUN expression. Likewise, inactivation of cJUN impairs the expression of GLI2. This mutual regulation occurs at the level of transcription with binding of cJUN and GLI2 to specific binding motifs. Interference with this mutual amplification of cJUN signaling and GLI2 signaling inhibits fibroblast activation and collagen release: Inhibition of cJUN/AP-1 signaling ameliorates hedgehog-induced fibroblast activation and skin fibrosis in SmoACT mice with a reduction of skin thickness of 103% (P = 0.0043) in the treatment group compared to the fibrotic control group. Moreover, combined pharmacologic inhibition of cJUN/AP-1 and hedgehog/GLI2 exerts additive antifibrotic effects in a model of TGFβ-driven experimental fibrosis (TBRACT mice). Conclusion: The transcription factors cJUN and GLI2 reinforce each other's activity to promote fibroblast activation in SSc. Interruption of this crosstalk by combined inhibition of both pathways exerts additive antifibrotic effects at well-tolerated doses.
CRIS-Team Scopus Importer:2024-12-06

NCOA3 AMPLIFIES PROFIBROTIC TRANSCRIPTIONAL PROGRAMS IN SYSTEMIC SCLEROSIS - Dees, Clara; Pötter, Sebastian; Fuchs, Maximilian; Bergmann, Christina; Matei, Alexandru-Emil; Györfi, Andrea-Hermina; Soare, A.; Ramming, Andreas; Ceppi, Paolo; Schett, Georg; Kunz, Meik; Distler, H. W. (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-09-24

Performance of serum biomarkers reflective of different pathogenic processes in systemic sclerosis-associated interstitial lung disease. - Györfi, Andrea Hermina; Filla, Tim; Dickel, Nicholas; Möller, Florian; Li, Yi Nan; Bergmann, Christina; Matei, Alexandru-Emil; Harrer, Thomas; Kunz, Meik; Schett, Georg; Distler, Jörg H.W. (Rheumatology, 2024)
OBJECTIVE: Interstitial lung disease (ILD) is the leading cause of mortality in SSc. Novel biomarkers are crucial to improve outcomes in SSc-ILD. We aimed to compare the performance of potential serum biomarkers of SSc-ILD that reflect different pathogenic processes: KL-6 and SP-D (epithelial injury), CCL18 (type 2 immune response), YKL-40 (endothelial injury and matrix remodelling) and MMP-7 (ECM remodelling). METHODS: Baseline and follow-up serum samples from 225 SSc patients were analysed by ELISA. Progressive ILD was defined according to the 2022-ATS/ERS/JRS/ALAT guidelines. Linear mixed models and random forest models were used for statistical analyses. RESULTS: Serum levels of KL-6 [MD 35.67 (95% CI 22.44-48.89, P < 0.01)], SP-D [81.13 (28.46-133.79, P < 0.01)], CCL18 [17.07 (6.36-27.77, P < 0.01)], YKL-40 [22.81 (7.19-38.44, P < 0.01)] and MMP-7 [2.84 (0.88-4.80, P < 0.01)] were independently associated with the presence of SSc-ILD. A machine-learning model including all candidates classified patients with or without ILD with an accuracy of 85%. The combination of KL-6 and SP-D was associated with the presence [0.77 (0.53-1.00, P' <0.01)] and previous progression of SSc-ILD [OR 1.28 (1.01-1.61, P' =0.047)]. Higher baseline levels of KL-6 [OR 3.70 (1.52-9.03, P < 0.01)] or SP-D [OR 2.00 (1.06-3.78, P = 0.03)] increased the odds of future SSc-ILD progression, independent of other conventional risk factors, and the combination of KL-6 and SP-D [1.109 (0.665-1.554, P < 0.01)] showed improved performance compared with KL-6 and SP-D alone. CONCLUSION: All candidates performed well as diagnostic biomarkers for SSc-ILD. The combination of KL-6 and SP-D might serve as biomarker for the identification of SSc patients at risk of ILD progression.
EVALuna2:538826

Plasma Metabolome Profiling for the Diagnosis of Catecholamine Producing Tumors - März, Juliane; Kurlbaum, Max; Roche-Lancaster, Oisin; Deutschbein, Timo; Peitzsch, Mirko; Prehn, Cornelia; Weismann, Dirk; Robledo, Mercedes; Adamski, Jerzy; Fassnacht, Martin; Kunz, Meik; Kroiss, Matthias (Frontiers in Endocrinology, 2021)
Context: Pheochromocytomas and paragangliomas (PPGL) cause catecholamine excess leading to a characteristic clinical phenotype. Intra-individual changes at metabolome level have been described after surgical PPGL removal. The value of metabolomics for the diagnosis of PPGL has not been studied yet. Objective: Evaluation of quantitative metabolomics as a diagnostic tool for PPGL. Design: Targeted metabolomics by liquid chromatography-tandem mass spectrometry of plasma specimens and statistical modeling using ML-based feature selection approaches in a clinically well characterized cohort study. Patients: Prospectively enrolled patients (n=36, 17 female) from the Prospective Monoamine-producing Tumor Study (PMT) with hormonally active PPGL and 36 matched controls in whom PPGL was rigorously excluded. Results: Among 188 measured metabolites, only without considering false discovery rate, 4 exhibited statistically significant differences between patients with PPGL and controls (histidine p=0.004, threonine p=0.008, lyso PC a C28:0 p=0.044, sum of hexoses p=0.018). Weak, but significant correlations for histidine, threonine and lyso PC a C28:0 with total urine catecholamine levels were identified. Only the sum of hexoses (reflecting glucose) showed significant correlations with plasma metanephrines. By using ML-based feature selection approaches, we identified diagnostic signatures which all exhibited low accuracy and sensitivity. The best predictive value (sensitivity 87.5%, accuracy 67.3%) was obtained by using Gradient Boosting Machine Modelling. Conclusions: The diabetogenic effect of catecholamine excess dominates the plasma metabolome in PPGL patients. While curative surgery for PPGL led to normalization of catecholamine-induced alterations of metabolomics in individual patients, plasma metabolomics are not useful for diagnostic purposes, most likely due to inter-individual variability.
CRIS-Team Scopus Importer:2021-10-01
Keywords: adrenal; catecholamines; feature selection; machine learning; mass spectronomy; paraganglioma; pheochromocytoma; targeted metabolomics

Plasma steroid metabolome profiling for the diagnosis of adrenocortical carcinoma - Schweitzer, Sophie; Kunz, Meik; Kurlbaum, Max; Vey, Johannes; Kendl, Sabine; Deutschbein, Timo; Hahner, Stefanie; Fassnacht, Martin; Dandekar, Thomas; Kroiss, Matthias (European Journal of Endocrinology, 2019)
Objective: Current workup for the pre-operative distinction between frequent adrenocortical adenomas (ACAs) and rare but aggressive adrenocortical carcinomas (ACCs) combines imaging and biochemical testing. We here investigated the potential of plasma steroid hormone profiling by liquid chromatography tandem mass spectrometry (LC-MS/MS) for the diagnosis of malignancy in adrenocortical tumors.
CRIS-Team WoS Importer:2019-02-21

Protein kinase C-β-dependent changes in the glucose metabolism of bone marrow stromal cells of chronic lymphocytic leukemia - Von Heydebrand, Franziska; Fuchs, Maximilian; Kunz, Meik; Kremer, Anita; Oostendorp, Robert A. J.; Wilke, Jochen; Leitges, Michael; Egle, Alexander; Mackensen, Andreas; Lutzny-Geier, Gloria; Völkl, Simon (Stem Cells, 2021)
Survival of chronic lymphocytic leukemia (CLL) cells critically depends on the support of an adapted and therefore appropriate tumor microenvironment. Increasing evidence suggests that B-cell receptor-associated kinases such as protein kinase C-β (PKCβ) or Lyn kinase are essential for the formation of a microenvironment supporting leukemic growth. Here, we describe the impact of PKCβ on the glucose metabolism in bone marrow stromal cells (BMSC) upon CLL contact. BMSC get activated by CLL contact expressing stromal PKCβ that diminishes mitochondrial stress and apoptosis in CLL cells by stimulating glucose uptake. In BMSC, the upregulation of PKCβ results in increased mitochondrial depolarization and leads to a metabolic switch toward oxidative phosphorylation. In addition, PKCβ-deficient BMSC regulates the expression of Hnf1 promoting stromal insulin signaling after CLL contact. Our data suggest that targeting PKCβ and the glucose metabolism of the leukemic niche could be a potential therapeutic strategy to overcome stroma-mediated drug resistance.
CRIS-Team Scopus Importer:2021-03-05
Keywords: BMSC; CLL; glucose metabolism; PKCβ

Reconstruction of the miR-506-Quaking axis in Idiopathic Pulmonary Fibrosis using integrative multi-source bioinformatics - Stojanović, Stevan D.; Fuchs, Maximilian; Liang, Chunguang; Schmidt, Kevin; Xiao, Ke; Just, Annette; Pfanne, Angelika; Pich, Andreas; Warnecke, Gregor; Braubach, Peter; Petzold, Christina; Jonigk, Danny; et al. (Scientific Reports, 2021)
The family of RNA-binding proteins (RBP) functions as a crucial regulator of multiple biological processes and diseases. However, RBP function in the clinical setting of idiopathic pulmonary fibrosis (IPF) is still unknown. We developed a practical in silico screening approach for the characterization of RBPs using multi-sources data information and comparative molecular network bioinformatics followed by wet-lab validation studies. Data mining of bulk RNA-Sequencing data of tissues of patients with IPF identified Quaking (QKI) as a significant downregulated RBP. Cell-type specific expression was confirmed by single-cell RNA-Sequencing analysis of IPF patient data. We systematically analyzed the molecular interaction network around QKI and its functional interplay with microRNAs (miRs) in human lung fibroblasts and discovered a novel regulatory miR-506-QKI axis contributing to the pathogenesis of IPF. The in silico results were validated by in-house experiments applying model systems of miR and lung biology. This study supports an understanding of the intrinsic molecular mechanisms of IPF regulated by the miR-506-QKI axis. Initially applied to human lung disease, the herein presented integrative in silico data mining approach can be adapted to other disease entities, underlining its practical relevance in RBP research.
CRIS-Team Scopus Importer:2021-06-25

Select hyperactivating NLRP3 ligands enhance the TH1-and TH17-inducing potential of human type 2 conventional dendritic cells - Hatscher, Lukas; Lehmann, Christian; Purbojo, Ariawan; Onderka, Constantin; Liang, Chunguang; Hartmann, Arndt; Cesnjevar, Robert; Bruns, Heiko; Gross, Olaf; Nimmerjahn, Falk; Burmazovic, Ivana Ivanovic; Kunz, Meik; et al. (Science Signaling, 2021)
The detection of microorganisms and danger signals by pattern recognition receptors on dendritic cells (DCs) and the consequent formation of inflammasomes are pivotal for initiating protective immune responses. Although the activation of inflammasomes leading to secretion of the cytokine IL-1 is typically accompanied by pyroptosis (an inflammatory form of lytic programmed cell death), some cells can survive and exist in a state of hyperactivation. Here, we found that the conventional type 2 DC (cDC2) subset is the major human DC subset that is transcriptionally and functionally poised for inflammasome formation and response without pyroptosis. When cDC2 were stimulated with ligands that relatively weakly activated the inflammasome, the cells did not enter pyroptosis but instead secreted IL-12 family cytokines and IL-1. These cytokines induced prominent T helper type 1 (TH1) and TH17 responses that were superior to those seen in response to Toll-like receptor (TLR) stimulation alone or to stronger, classical inflammasome ligands. These findings not only define the human cDC2 subpopulation as a prime target for the treatment of inflammasome-dependent inflammatory diseases but may also inform new approaches for adjuvant and vaccine development.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Dendritic cells; cDC2; CD1c; inflammasome; hyperactivation; L18-MDP; T cell differentiation

Select hyperactivating NLRP3 ligands enhance the TH1-and TH17-inducing potential of human type 2 conventional dendritic cells - Heger, Lukas; Hatscher, Lukas; Lehmann, Christian; Purbojo, Ariawan; Onderka, Constantin; Liang, C.; Hartmann, Arndt; Cesnjevar, Robert; Bruns, Heiko; Gross, O.; Nimmerjahn, Falk; Ivanovic-Burmazovic, I.; et al. (EXPERIMENTAL DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-03-04

Soluble CD83 improves and accelerates wound healing by the induction of pro-resolving macrophages - Royzman, Dmytro; Peckert-Maier, Katrin; Stich, Lena; König, Christina; Wild, Andreas; Tauchi, Miyuki; Ostalecki, Christian; Kiesewetter, Franklin; Seyferth, Stefan; Lee, Geoffrey; Eming, Sabine A.; Fuchs, Maximilian; et al. (Frontiers in Immunology, 2022)
To facilitate the recovery process of chronic and hard-to-heal wounds novel pro-resolving treatment options are urgently needed. We investigated the pro-regenerative properties of soluble CD83 (sCD83) on cutaneous wound healing, where sCD83 accelerated wound healing not only after systemic but also after topical application, which is of high therapeutic interest. Cytokine profile analyses revealed an initial upregulation of inflammatory mediators such as TNFα and IL-1β, followed by a switch towards pro-resolving factors, including YM-1 and IL-10, both expressed by tissue repair macrophages. These cells are known to mediate resolution of inflammation and stimulate wound healing processes by secretion of growth factors such as epidermal growth factor (EGF) and vascular endothelial growth factor (VEGF), which promote vascularization as well as fibroblast and keratinocyte differentiation. In conclusion, we have found strong wound healing capacities of sCD83 beyond the previously described role in transplantation and autoimmunity. This makes sCD83 a promising candidate for the treatment of chronic- and hard-to-heal wounds.
CRIS-Team Scopus Importer:2022-10-28
Keywords: CD83; macrophages; stem cells; therapy; tissue regeneration; wound healing

Soluble CD83 modulates human-monocyte-derived macrophages toward alternative phenotype, function, and metabolism. - Peckert-Maier, Katrin; Wild, Andreas; Sprißler, Laura; Fuchs, Maximilian; Beck, Philipp; Auger, Jean-Philippe; Sinner, Pia; Strack, Astrid; Mühl-Zürbes, Petra; Ramadan, Ntilek; Kunz, Meik; Krönke, Gerhard; et al. (Frontiers in Immunology, 2023)
Alterations in macrophage (Mφ) polarization, function, and metabolic signature can foster development of chronic diseases, such as autoimmunity or fibrotic tissue remodeling. Thus, identification of novel therapeutic agents that modulate human Mφ biology is crucial for treatment of such conditions. Herein, we demonstrate that the soluble CD83 (sCD83) protein induces pro-resolving features in human monocyte-derived Mφ biology. We show that sCD83 strikingly increases the expression of inhibitory molecules including ILT-2 (immunoglobulin-like transcript 2), ILT-4, ILT-5, and CD163, whereas activation markers, such as MHC-II and MSR-1, were significantly downregulated. This goes along with a decreased capacity to stimulate alloreactive T cells in mixed lymphocyte reaction (MLR) assays. Bulk RNA sequencing and pathway analyses revealed that sCD83 downregulates pathways associated with pro-inflammatory, classically activated Mφ (CAM) differentiation including HIF-1A, IL-6, and cytokine storm, whereas pathways related to alternative Mφ activation and liver X receptor were significantly induced. By using the LXR pathway antagonist GSK2033, we show that transcription of specific genes (e.g., PPARG, ABCA1, ABCG1, CD36) induced by sCD83 is dependent on LXR activation. In summary, we herein reveal for the first time mechanistic insights into the modulation of human Mφ biology by sCD83, which is a further crucial preclinical study for the establishment of sCD83 as a new therapeutical agent to treat inflammatory conditions.
EVALuna2:549687

The new genetic landscape of cushing’s disease: Deubiquitinases in the spotlight - Sbiera, Silviu; Kunz, Meik; Weigand, Isabel; Deutschbein, Timo; Dandekar, Thomas; Fassnacht, Martin (Cancers, 2019)
Cushing’s disease (CD) is a rare condition caused by adrenocorticotropic hormone (ACTH)-producing adenomas of the pituitary, which lead to hypercortisolism that is associated with high morbidity and mortality. Treatment options in case of persistent or recurrent disease are limited, but new insights into the pathogenesis of CD are raising hope for new therapeutic avenues. Here, we have performed a meta-analysis of the available sequencing data in CD to create a comprehensive picture of CD’s genetics. Our analyses clearly indicate that somatic mutations in the deubiquitinases are the key drivers in CD, namely USP8 (36.5%) and USP48 (13.3%). While in USP48 only Met415 is affected by mutations, in USP8 there are 26 different mutations described. However, these different mutations are clustering in the same hotspot region (affecting in 94.5% of cases Ser718 and Pro720). In contrast, pathogenic variants classically associated with tumorigenesis in genes like TP53 and BRAF are also present in CD but with low incidence (12.5% and 7%). Importantly, several of these mutations might have therapeutic potential as there are drugs already investigated in preclinical and clinical setting for other diseases. Furthermore, network and pathway analyses of all somatic mutations in CD suggest a rather unified picture hinting towards converging oncogenic pathways.
CRIS-Team Scopus Importer:2019-11-19
Keywords: Cushing’s disease; Deubiquitinases; Pathogenesis; Somatic mutations

Tumor microenvironment-dependent epigenetic imprinting in the vasculature predicts colon cancer outcome - Naschberger, Elisabeth; Fuchs, Maximilian; Dickel, Nicholas; Kunz, Meik; Popp, Bernt; Anchang, Charles Gwellem; Demmler, Richard; Lyu, Yanmin; Uebe, Steffen; Ekici, Arif Bülent; Geppert, Carol-Immanuel; Hartmann, Arndt; et al. (Cancer Communications, 2023)
CRIS-Team Scopus Importer:2023-10-27

XCR1 expression distinguishes human conventional dendritic cell type 1 with full effector functions from their immediate precursors - Heger, Lukas; Hatscher, Lukas; Liang, Chunguang; Lehmann, Christian; Amon, Lukas; Lühr, Jennifer J.; Kaszubowski, Tomasz; Nzirorera, Rayk; Schaft, Niels; Dörrie, Jan; Irrgang, Pascal; Tenbusch, Matthias; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Dendritic cells (DCs) are major regulators of innate and adaptive immune responses. DCs can be classified into plasmacytoid DCs and conventional DCs (cDCs) type 1 and 2. Murine and human cDC1 share the mRNA expression of XCR1. Murine studies indicated a specific role of the XCR1-XCL1 axis in the induction of immune responses. Here, we describe that human cDC1 can be distinguished into XCR1- and XCR1+ cDC1 in lymphoid as well as nonlymphoid tissues. Steady-state XCR1+ cDC1 display a preactivated phenotype compared to XCR1- cDC1. Upon stimulation, XCR1+ cDC1, but not XCR1- cDC1, secreted high levels of inflammatory cytokines as well as chemokines. This was associated with enhanced activation of NK cells mediated by XCR1+ cDC1. Moreover, XCR1+ cDC1 excelled in inhibiting replication of Influenza A virus. Further, under DC differentiation conditions, XCR1- cDC1 developed into XCR1+ cDC1. After acquisition of XCR1 expression, XCR1- cDC1 secreted comparable level of inflammatory cytokines. Thus, XCR1 is a marker of terminally differentiated cDC1 that licenses the antiviral effector functions of human cDC1, while XCR1- cDC1 seem to represent a late immediate precursor of cDC1.
CRIS-Team Scopus Importer:2023-08-25
Keywords: antiviral immunity; cDC1; DC differentiation; IL-12; XCR1